2007
DOI: 10.1097/00001199-200701000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Service Needs of Persons With Traumatic Brain Injury

Abstract: Many persons experiencing TBI report having unmet service needs 1 year after hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 45 publications
6
98
1
Order By: Relevance
“…Managing emotions and behaviors in this study was also consistent with previous studies that identified stress, emotional upsets, and moodiness as frequent needs and concerns of people with TBI [27][28]30,32,34]. Lefebvre et al was the only study mentioned previously that reported needs and concerns related to people with TBI's uncertainty about the future of their disabilities [28].…”
Section: Needs and Concernssupporting
confidence: 89%
See 4 more Smart Citations
“…Managing emotions and behaviors in this study was also consistent with previous studies that identified stress, emotional upsets, and moodiness as frequent needs and concerns of people with TBI [27][28]30,32,34]. Lefebvre et al was the only study mentioned previously that reported needs and concerns related to people with TBI's uncertainty about the future of their disabilities [28].…”
Section: Needs and Concernssupporting
confidence: 89%
“…Consistent with the current results, other studies have found that obtaining employment, improving job skills, and increasing educational qualifications were relevant needs and concerns reported by people with TBI [27,30,34]. Financial challenges, managing money, and paying bills are common needs and concerns reported in the literature of people with TBI [27,[29][30]32,35].…”
Section: Needs and Concernssupporting
confidence: 89%
See 3 more Smart Citations